Fixed target combined with spectral mapping: approaching 100% hit rates for serial crystallography. Issue 8 (4th August 2016) - Oghbaey, Saeed; Sarracini, Antoine; Ginn, Helen M.; Pare-Labrosse, Olivier; Kuo, Anling; Marx, Alexander; Epp, Sascha W.; Sherrell, Darren A.; Eger, Bryan T.; Zhong, Yinpeng; Loch, Rolf; Mariani, Valerio; et al.
Abstract : A sample‐delivery system featuring high hit rates, low background and minimal sample requirements is presented for serial crystallography at XFELs and synchrotrons. Abstract : The advent of ultrafast highly brilliant coherent X‐ray free‐electron laser sources has driven the development of novel structure‐determination approaches for proteins, and promises visualization of protein dynamics on sub‐picosecond timescales with full atomic resolution. Significant efforts are being applied to the development of sample‐delivery systems that allow these unique sources to be most efficiently exploited for high‐throughput serial femtosecond crystallography. Here, the next iteration of a fixed‐target crystallography chip designed for rapid and reliable delivery of up to 11 259 protein crystals with high spatial precision is presented. An experimental scheme for predetermining the positions of crystals in the chip by means of in situ spectroscopy using a fiducial system for rapid, precise alignment and registration of the crystal positions is presented. This delivers unprecedented performance in serial crystallography experiments at room temperature under atmospheric pressure, giving a raw hit rate approaching 100% with an effective indexing rate of approximately 50%, increasing the efficiency of beam usage and allowing the method to be applied to systems where the number of crystals is limited.